Fighting against the Odds: An Insider's Life in UFC, Boxing, and Entertainment - Rafiq, Fiaz (Rowman & Littlefield Publishers, 2022)
A riveting memoir by acclaimed combat sports and entertainment journalist Fiaz Rafiq, as he shares captivating stories of fighting legends and entertainment stars alongside the story of his own personal hardships, struggles against prejudice, and ultimate triumph. Fighting against the Odds is the culmination of Fiaz Rafiq’s decades of work behind the scenes as a mixed martial arts and combat sports journalist, gaining the trust and confidence of the best fighters in UFC and boxing. Rafiq shares candid accounts, hidden histories, and thrilling experiences from his time with some of the most famous and prominent personalities in fighting sports. Included are never-before-told stories of UFC’s most decorated and revered champions in Randy Couture, Royce Gracie, Daniel Cormier, Brock Lesnar, Georges St-Pierre, and Conor McGregor and boxing and martial arts icons such as Mike Tyson, Muhammad Ali, and Bruce Lee. Reaching the pinnacle of his career was anything but a smooth ride for Rafiq. The writer faced adversities, obstacles, and even harassment at American airports. Fighting against the Odds is a fascinating odyssey, one man’s inspiring coming-of-age story populated by some of the most colorful characters in the world of sports and entertainment. Itis a powerful story of hard work, tenacity, and success against overwhelming odds.